A property-performance correlation and mass transfer study of As(v) adsorption on three mesoporous aluminas. Issue 84 (26th August 2016) - Dou, Xiaomin; Li, Yonghuan; Mohan, Dinesh; Pittman, Charles U.; Hu, Meng
Abstract : The order of long-range atomic arrangement obviously decreases in the order MA3 > MA2 > MA1 and is inversely correlated with the adsorption abilities of these aluminas. Therefore, strongly disordered atomic arrangements enhance the As(v ) uptake abilities of these aluminas. Abstract : High adsorption capacity and quick adsorption kinetics are necessary for excellent adsorbents. Three different mesoporous aluminas (MA) were extensively characterized to determine their key structural properties that account for their good adsorption capacities and fast kinetics for sequestering As(v ) from water. MA1 showed the largest As(v ) adsorption capacity of 175.7 mg g −1 among the three. No direct relationship was observed between the mesoporous pore properties and the adsorption capacities of these mesoporous aluminas. The extraordinarily large adsorption capacity of MA1 was correlated to its strongly disordered state confirmed by a pair distribution function (PDF) analysis, its large amorphous content fraction measured by selective chemical extraction (SCE), its high Al–OH surface site density determined by a surface titration method, and its Al–O coordination environment (AlO4 and AlO5 ) identified by 27 Al NMR. These results led to the realization that extensive structural disorder, large amorphous content and high surface site density are preferred in future adsorbent preparations. Besides its excellent adsorption capacity, MA1 also had the fastest adsorption kinetics. All As(v ) uptake kinetics data were modeled using the homogeneous surface diffusion model (HSDM). The intraparticle surface diffusion coefficients ( D s ) were numerically determined. The fast As(v ) uptake kinetics of MA1 were explained by it having the smallest particle size from the HSDM calculations. Decreasing solution pH significantly improved the As(v ) treatment efficiencies. Maximum sorption occurred at pH below 5.0. MA1 effectively decreased As(v ) concentrations in spiked well water to well below the WHO's maximum level of As(v ) in drinking water, indicating its great potential as a practical adsorbent candidate.